Gemcitabine‐based adjuvant chemotherapy in subtypes of ampullary adenocarcinoma: international propensity score‐matched cohort study. Issue 9 (7th April 2020) - Moekotte, A. L.; Malleo, G.; van Roessel, S.; Bonds, M.; Halimi, A.; Zarantonello, L.; Napoli, N.; Dreyer, S. B.; Wellner, U. F.; Bolm, L.; Mavroeidis, V. K.; Robinson, S.; et al.
Abstract : Background: Whether patients who undergo resection of ampullary adenocarcinoma have a survival benefit from adjuvant chemotherapy is currently unknown. The aim of this study was to compare survival between patients with and without adjuvant chemotherapy after resection of ampullary adenocarcinoma in a propensity score‐matched analysis. Methods: An international multicentre cohort study was conducted, including patients who underwent pancreatoduodenectomy for ampullary adenocarcinoma between 2006 and 2017, in 13 centres in six countries. Propensity scores were used to match patients who received adjuvant chemotherapy with those who did not, in the entire cohort and in two subgroups (pancreatobiliary/mixed and intestinal subtypes). Survival was assessed using the Kaplan–Meier method and Cox regression analyses. Results: Overall, 1163 patients underwent pancreatoduodenectomy for ampullary adenocarcinoma. After excluding 187 patients, median survival in the remaining 976 patients was 67 (95 per cent c.i. 56 to 78) months. A total of 520 patients (53·3 per cent) received adjuvant chemotherapy. In a propensity score‐matched cohort (194 patients in each group), survival was better among patients who received adjuvant chemotherapy than in those who did not (median survival not reached versus 60 months respectively; P  = 0·051). A survival benefit was seen in patients with the pancreatobiliary/mixed subtype; median survival was not reached in patients receiving adjuvant chemotherapy and 32 months in the group without chemotherapy ( P =  0·020). Patients with the intestinal subtype did not show any survival benefit from adjuvant chemotherapy. Conclusion: Patients with resected ampullary adenocarcinoma may benefit from gemcitabine‐based adjuvant chemotherapy, but this effect may be reserved for those with the pancreatobiliary and/or mixed subtype. Abstract : In this retrospective international multicentre study, patients with resected ampullary adenocarcinoma of the pancreaticobiliary/mixed subtype demonstrated a survival benefit from adjuvant chemotherapy. No benefit seemed present for the intestinal subtype. Selection is key Abstract : Antecedentes: Actualmente se desconoce si la quimioterapia adyuvante ofrece un beneficio en la supervivencia de los pacientes que se someten a resección de un adenocarcinoma ampular. El objetivo de este estudio fue comparar la supervivencia mediante la concordancia estimada por emparejamiento por puntaje de propensión, entre pacientes con y sin quimioterapia adyuvante después de la resección de un adenocarcinoma ampular. Métodos: Se realizó un estudio internacional de cohortes multicéntrico, que incluyó a los pacientes que se sometieron a una duodenopancreatectomía por adenocarcinoma ampular (2006‐2017) en 13 centros de seis países. Los puntajes de propensión se usaron para emparejar a los pacientes que recibieron quimioterapia adyuvante con los que no; tanto en la cohorte completa como en dos subgrupos (subtipo pancreaticobiliar / mixto e intestinal). La supervivencia se evaluó utilizando el método de Kaplan‐Meier y las regresiones de Cox. Resultados: En total, 1.163 pacientes fueron sometidos a una duodenopancreatectomía por adenocarcinoma ampular. Después de excluir a 179 pacientes, la mediana de supervivencia de los 976 pacientes restantes fue de 67 meses (i.c. del 95%, 56‐78), de los cuales un total de 520 pacientes (53%) recibieron quimioterapia adyuvante. En una cohorte de emparejamiento por puntaje de propensión (194 versus 194 pacientes), la mediana de supervivencia fue mejor en los pacientes tratados con quimioterapia adyuvante en comparación con aquellos sin quimioterapia adyuvante (no se alcanzó la mediana de supervivencia versus 60 meses, respectivamente; P = 0, 051). En el subtipo pancreaticobiliar/mixto se observó un beneficio en la supervivencia; no se alcanzó la mediana de supervivencia en pacientes que recibieron quimioterapia adyuvante versus 32 meses en el grupo sin quimioterapia, P = 0, 020. El subtipo intestinal no mostró beneficio en la supervivencia de la quimioterapia adyuvante. Conclusión: Los pacientes con adenocarcinoma ampular resecado pueden beneficiarse de la quimioterapia adyuvante basada en gemcitabina, pero este efecto podría reservarse para aquellos pacientes con subtipo de tumor pancreaticobiliar y/o mixto.